2014
DOI: 10.1309/ajcp2ry1pirrpuow
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Local International Sensitivity Index Systems for Monitoring Warfarin and Liver function

Abstract: Local ISI determined by a commercial local calibrator improved INR standardization among thromboplastins. The alternative ISI calibration using liver-specific calibration plasma is expected to reduce INR variability for the evaluation of liver function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…1,2 With the automatization of laboratories, several studies have shown that the ISI of thromboplastin may also vary, depending on the instrument used. Consequently, a reagent-or instrument-specific ISI was introduced.…”
Section: Baccouche Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 With the automatization of laboratories, several studies have shown that the ISI of thromboplastin may also vary, depending on the instrument used. Consequently, a reagent-or instrument-specific ISI was introduced.…”
Section: Baccouche Et Almentioning
confidence: 99%
“…In addition, it has been suggested to determine the local ISI for each reagent/instrument combination. 1 Currently, biologists often wish to know whether changing the instrument or the reagent has any impact on INR results. As there is no "reference" combination, a new one must be compared to the older one.…”
Section: Baccouche Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Procedures for using INR calibrants are described in CLSI document H-54 [9]. Local INR calibration using plasma calibrants is appealing from both a theoretical perspective and the documented deficiencies of the INR schema, and the use of INR calibrants improves INR accuracy and decreases interlaboratory variation [11][12][13][14][15][16][17]. However, calibrants are not available in the United States for most coagulation test systems.…”
Section: Plasma Calibrantsmentioning
confidence: 99%
“…Este exame foi amplamente utilizado nas últimas décadas para avaliar e predizer o risco de sangramento em pacientes com cirrose, pois ele representa a redução dos níveis desses fatores procoagulantes na cirrose. A conversão dos resultados do TP para a escala international normalized ratio (INR) é validada apenas para a monitorização de pacientes em anticoagulação com antagonistas da vitamina K e o resultado está sujeito a ampla variabilidade (57,58) . Com o intuito melhorar a reprodutibilidade do INR em pacientes com cirrose, foi descrita uma padronização metodológica diferenciada, denominada na literatura de INR-Liver (59) .…”
Section: Testes Convencionaisunclassified